2023
DOI: 10.1021/acs.analchem.3c01624
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Genetically Encoded Light-Up RNA Aptamers for Label-free and Ultrasensitive Detection of CircRNAs in Cancer Cells and Tissues

Ning-ning Zhao,
Feng-zheng Li,
Xinyi Zhang
et al.

Abstract: Circular RNAs (circRNAs) as endogenous non-coding RNAs are characterized by covalently closed circular structures, and they widely exist in mammalian cells. The aberrant expression of circRNAs may result in various diseases. Herein, we demonstrate the construction of genetically encoded light-up RNA aptamers for ultrasensitive and label-free detection of circRNA mitochondrial tRNA translation optimization 1 (circMTO1) in cancer cells and tissues. The lightup RNA aptamers are generated by proximity ligation-act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…successfully demonstrated that breast cancer patients have higher circMTO1 expression levels using a fluorescent detection strategy. [ 47 ] What is more, high expression of plasma exosome circPDE8A correlates with tumor progression and prognosis and would be used as a promising diagnostic or progression biomarker for Pancreatic ductal adenocarcinoma (PDAC). [ 48 ] However, the detection of circRNAs still faces great challenges.…”
Section: Conventional Exosomal Biomarkersmentioning
confidence: 99%
“…successfully demonstrated that breast cancer patients have higher circMTO1 expression levels using a fluorescent detection strategy. [ 47 ] What is more, high expression of plasma exosome circPDE8A correlates with tumor progression and prognosis and would be used as a promising diagnostic or progression biomarker for Pancreatic ductal adenocarcinoma (PDAC). [ 48 ] However, the detection of circRNAs still faces great challenges.…”
Section: Conventional Exosomal Biomarkersmentioning
confidence: 99%
“…The qRT-PCR can readily quantify circRNA with relatively high sensitivity, but it involves reverse transcription that is susceptible to contamination. To overcome these drawbacks, a series of fluorescent and electrochemical methods integrated with nucleic acid amplification strategies (e.g., duplex-specific nuclease-mediated cycling amplification, , loop-mediated isothermal amplification, , catalytic hairpin assembly, primer exchange reaction, hybridization chain reaction, and recombinase polymerase amplification) have been developed for circRNA assay with merits of improved sensitivity and more flexible sensing modes. However, these methods inevitably involve costly fluorophore/quencher dual-labeled signal probes, superabundant enzymes, and time-consuming operational procedures.…”
mentioning
confidence: 99%